Reduccion de CO2 por el Uso de Lamparas de Bajo Consumo a Expensas de la Generacion de Residuos Peligrosos Domiciliarios - Parente, Jorge R.; Leanza, Luis N. (KnE Engineering, 2018)
Because the national legislation prohibits the sale of incandescent lamps the argentine citizen can acquire compact fluorescent lamps in their replacement. This situation has led us to develop this work whose main objective is to establish a comparison between these two types of lamps from the energy point of view and its environmental consequences. To this end, we have developed a study based on the last national census in Argentina. While significant energy savings achieved, and as a result lower emissions of carbon dioxide, this leads to an environmental problem due to the mercury content of compact fluorescent lamps. They become in hazardous waste when exhausted their useful lives and are discarded in sites for municipal solid waste. High probability that the lamps are broken and release mercury that can contaminate 19,55 liters of drinking water for kilogram of CO2 saved. We conclude that the regulations required to purchase compact fluorescent lamps instead of traditional incandescent lamps must go accompanied with sustainable alternatives to dispose them appropriately since otherwise we will be replacing an environmental problem with another.